Application of phosphoric acid and phytic acid doped polybenzimidazole for high temperature proton exchange membrane fuel cell - Daud, Nur Anati Bazilah (2022)
An increase demand of energy supply has become the main concern since the conventional fossil fuels is exhaustive in supplies. Literature shows that proton exchange membrane fuel cell (PEMFC) has been receiving attention for various stationary and transportation application. Polybenzimidazoles-phosphoric acid (PBI/PA) has gaining attention to become a membrane for High Temperature Proton Exchange Membrane Fuel Cell (HT-PEMFC) applications. However, there have been concerns on the durability and stability of PBI/PA membrane system, which negatively affect their widespread used for commercialization. The problems include the PA leaching from PEM that lead to proton conductivity decay as well as deterioration of PEMFC performance during long-term operation. Therefore, the aim of this research is to develop a new PBI/Acid membrane containing highly phosphonated phytic acid (PyA) (C6H18O24P6) molecules as a co-dopant acid of PA. The presence of abundance hydrophilic hydroxyl groups around the cyclohexane ring of PyA molecule is expected to be able to participate in H bonding interactions with the functionalities in PBI/PA matrix and hence help to improve its stability and durability. The analyses of this newly PBI/Acid membrane system were carried out using Fourier- transform infrared (FTIR), X-ray diffraction (XRD), and thermogravimetric analysis (TGA). Based on the analysis, the synthesized PBI doped acid membrane followed the required properties for HT-PEMFC application, which is stable up to 500 °C, in which significantly higher than the operating temperature of HT-PEMFC. To address the issue on proton conductivity decay, PBI membranes with different porosity were fabricated as a sponge-like porous structure membrane has the ability to the absorb excess acids. Porous PBI-1 (pPBI-1) and porous PBI-5 (pPBI-5) membranes which represent 1 wt% and 5 wt% additional of porogenic solvent were successfully fabricated. Six different acid doping conditions, which varied time and temperature were applied and the acid doped membranes were evaluated based on their acid doping level (ADL) behaviour with respect to the proton conductivity value. The results showed that porous PBI membrane with higher porosity contributed to higher ADL values, which resulted in higher proton conductivity value. In addition, the membrane were tested under different relative humidity (RH), and the results indicate that the proton conductivity increases significantly with RH and temperature. Subsequently, the single cell test of HT-PEMFC was conducted and the performance of the selected doping condition of porous PBI/Acid doped membranes (from doping Condition 6) was evaluated following the requirement of HT-PEMFC operation. The performance of the membranes tested for HT-PEMFC showed that porous PBI membrane with lower porosity exhibiting better performance than the porous PBI membrane with higher porosity. Therefore, it can be concluded that both pPBI-1 and pPBI-5 gave an excellent performance in their respective ways and based on the membrane evaluation performance, PBI membrane doped with both PA and PyA have the potential to be used as a doping solution for HT-PEMFC.